Bonded concrete overlays as a rehabilitation alternative for asphalt pavements - Espinoza Alfaro, Marianela (2016)
The main objective of this study, is to present basic considerations while designing a concrete overlay as a rehabilitation alternative for existing pavements. First, the pavement condition has to be evaluated by determining the type of damage, previous repairs, and the need for surface preparation; then it is necessary to evaluate the possibilities for the application of this technique. Bonded concrete overlays are a sustainable strategy to preserve and extend the life of pavements that can be used as minor rehabilitation, which its main purpose is to add structural capacity and to eliminate surface damage on existing pavements by creating an adequate bond between the concrete overlay and the pavement structure. High deterioration levels have been identified on pavement structures in Costa Rica, which make up most of the roads in the national road network, where quite often feasible solution alternatives are not considered due to a lack of knowledge. Therefore, this literature review focuses on the use of bonded concrete overlays, considering the construction requirements, as well as the design methodologies. This paper intends to provide road engineers with a reference document to help in deciding the most adequate solution to common problems found on existing pavements, in order to increase knowledge in this area, to encourage the use of new techniques to improve road infrastructure, therefore improve the quality of service provided to the user.